Alien and native fish in gill nets at Rhodes, eastern Mediterranean (2014–2015). (16th May 2017) - Corsini-Foka, Maria; Mastis, Stefanos; Kondylatos, Gerasimos; Batjakas, Ioannis E.
Abstract : Fish catch composition in 21 gill net samplings performed between 2014 and 2015 at Rhodes Island (Aegean Sea, Greece) was analysed, with the aim to contribute in filling scattered information on coastal fish assemblages in a Mediterranean region heavily impacted by biological invasions. A total biomass of 183 kg was collected comprising 1070 fish individuals, distributed along 43 native and six Lessepsian migrant species. The alien Siganus luridus prevailed in terms of frequency of occurrence, followed by the native Sparisoma cretense, which exhibited the higher abundance and biomass, followed by S. luridus, Scorpaena scrofa and Siganus rivulatus . Ratios between alien and native species as well as between their abundance and biomass are discussed.